2019
DOI: 10.1111/ejh.13283
|View full text |Cite
|
Sign up to set email alerts
|

Common oral diseases, hyposalivation and survival post‐HSCT, a longitudinal study

Abstract: Objectives Haematopoietic stem cell transplantation (HSCT) recipients are at risk of side effects within the oral cavity. The purpose of this study was to examine progression of common oral diseases and hyposalivation and their associations with survival in allogeneic HSCT recipients. Methods Two hundred and sixty nine adult HSCT recipients treated with HSCT between 2008 and 2016 were included in this study. The associations of caries, decayed, missing, filled teeth (DMFT) index, radiological attachment loss a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 42 publications
(175 reference statements)
2
17
1
Order By: Relevance
“…was 17.1, and the mean number of decayed surfaces was 1.4 (SD: 2.2), which is in line with a Dutch population of comparable age groups [Vermaire and Schuller, 2019]. Previous publications reported a broad range of DMFT scores before autologous and allogeneic HSCT, varying between 7.0 [Ertas et al, 2014] and 18.9 [Uutela et al, 2019a]. These broad variations might reflect differences in patient selection and oral health care systems in different countries and emphasize the difficulties when comparing different populations of HSCT recipients.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…was 17.1, and the mean number of decayed surfaces was 1.4 (SD: 2.2), which is in line with a Dutch population of comparable age groups [Vermaire and Schuller, 2019]. Previous publications reported a broad range of DMFT scores before autologous and allogeneic HSCT, varying between 7.0 [Ertas et al, 2014] and 18.9 [Uutela et al, 2019a]. These broad variations might reflect differences in patient selection and oral health care systems in different countries and emphasize the difficulties when comparing different populations of HSCT recipients.…”
Section: Discussionsupporting
confidence: 84%
“…The SWS flow rate of patients with caries progression was over time 26% lower in comparison to patients without caries progression. Recently, it was concluded that caries prevalence was consistently but not significantly higher in patients with hyposalivation 6, 12, and 24 months post-HSCT [Uutela et al, 2019a].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hematopoietic cell transplantation (HCT) is the treatment of choice for a number of malignant and non‐malignant diseases involving the hematopoietic system and for some solid tumours (Gratwohl et al., 2011; Passweg et al., 2012). The treatment is, however, often associated with several oral side effects including oral mucositis, oral infections, alterations in taste and in saliva quantity and composition (Passweg et al., 2012; Sonis et al., 2001, 2004; Uutela et al., 2019). Graft‐versus‐host disease (GVHD) is a common complication of allogenic HCT (allo‐HCT), affecting multiple organ systems and causing significant morbidity and mortality (Kuten‐Shorrer et al., 2014; Lee et al., 2003; Presland, 2017).…”
Section: Introductionmentioning
confidence: 99%